2016
DOI: 10.1016/j.celrep.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Vav Proteins Are Key Regulators of Card9 Signaling for Innate Antifungal Immunity

Abstract: SummaryFungal infections are major causes of morbidity and mortality, especially in immunocompromised individuals. The innate immune system senses fungal pathogens through Syk-coupled C-type lectin receptors (CLRs), which signal through the conserved immune adaptor Card9. Although Card9 is essential for antifungal defense, the mechanisms that couple CLR-proximal events to Card9 control are not well defined. Here, we identify Vav proteins as key activators of the Card9 pathway. Vav1, Vav2, and Vav3 cooperate do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 67 publications
1
50
0
Order By: Relevance
“…The authors showed that treatment strategies involving the inhibition of CBLB led to increased inflammatory responses and improved the outcome of experimental candidiasis, which provides evidence that CBLB might represent a therapeutic target in fungal disease. Furthermore, it has been found that another ubiquitin ligase TRIM62 as well as Vav proteins regulate CARD9-mediated antifungal immunity, and these molecules are also potential therapeutic targets [10, 11]. Vav proteins are key activators of the CARD9 pathway by cooperating downstream of dectin-1 to engage CARD9 for NF-κB control and proinflammatory gene transcription, while TRIM62 acts as a CARD9-binding partner facilitating CARD9 poly­ubiquitination, which is essential for its activity.…”
Section: Dectin-1mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed that treatment strategies involving the inhibition of CBLB led to increased inflammatory responses and improved the outcome of experimental candidiasis, which provides evidence that CBLB might represent a therapeutic target in fungal disease. Furthermore, it has been found that another ubiquitin ligase TRIM62 as well as Vav proteins regulate CARD9-mediated antifungal immunity, and these molecules are also potential therapeutic targets [10, 11]. Vav proteins are key activators of the CARD9 pathway by cooperating downstream of dectin-1 to engage CARD9 for NF-κB control and proinflammatory gene transcription, while TRIM62 acts as a CARD9-binding partner facilitating CARD9 poly­ubiquitination, which is essential for its activity.…”
Section: Dectin-1mentioning
confidence: 99%
“…Vav proteins are key activators of the CARD9 pathway by cooperating downstream of dectin-1 to engage CARD9 for NF-κB control and proinflammatory gene transcription, while TRIM62 acts as a CARD9-binding partner facilitating CARD9 poly­ubiquitination, which is essential for its activity. Moreover, TRIM62- as well as Vav1/2/3-deficient mice exhibit extreme susceptibility to Candida infection, suggesting that they have a pivotal role in antifungal immunity [10, 11]. Interestingly, CD23, a novel CLR, which is well known for its function as a low-affinity receptor for IgE, plays an important role in antifungal immunity through recognition of surface components of fungal pathogens, such as α-mannan and β-glucan, leading to upregulation of nitric oxide synthase (NOS2) expression, reactive oxygen species (ROS) production, and fungal killing.…”
Section: Dectin-1mentioning
confidence: 99%
“…5 and SUPP. Table 2) (40)(41)(42). A divergent noncoding transcript (9130024F11Rik) that shares a promoter with SATB2 is also highly upregulated (SUPP.…”
Section: Specific Activation Of Rig-i By Slr and Poly(i:c) Reveals A mentioning
confidence: 99%
“…Interestingly, a survey of invertebrate Dectin-1 C-lectin domain homologs finds back top-scoring hits from mollusks and cnidarians but not the much better characterized arthropod and nematode genomes (Pees et al 2016), similar to previous observations (Wood-Charlson and Weis 2009). Recently, the vav1-3 proteins were found to be critical for CARD9 signaling downstream of lectin receptors (Roth et al 2016), and also these proteins are more similar in cnidarians and lophotrochozoans compared to other invertebrates. C-type lectins are already associated to innate immunity in mollusks and cnidarians (Vidal-Dupiol et al 2009).…”
Section: Itam Receptors and Syk : A Potential Original Pathway For Thmentioning
confidence: 99%